Glomus tumor of the anterior urethra: A rare case report and review of the literature - HE, TAO (Mol Clin Oncol, 2016)
Glomus tumors are rare and benign neoplasms, which normally originate from peripheral soft tissue. To date, reported cases of glomus tumor occurring in genitourinary tract, particularly in the urethra, are exceedingly rare. The present study presented a rare case of glomus tumor of the anterior urethra in a 42 year-old male, his main complaints were a history of anterior urethra pain for 3 years, and a palpable and tender mass in the urethra for 2 weeks. Urethrocystoscopy examination and the resection of the urethral mass were performed. Pathological and immunohistochemical examination revealed that the mass was a benign glomus tumor. The patient remained in good condition by 6 month follow-up, and revealed no problems or recurrence following surgery. This is the first case, to the best of our knowledge, to present a glomus tumor occurring in a male's urethra and the present report provided a supplementary review for the previous cases and the literature.